Coach to coach : an empowering story about how to be a great leader - Rooney, Martin, 1971- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
"The world needs better coaches. If Martin Rooney asked you to name the top 20 basketball, football or baseball players of all time, he doesn't think you would have a problem quickly rattling off a comprehensive list. Granted your list might not be the same as everyone else's, but I it wouldn't be too difficult for you to come up with a bunch of names in a short period of time. But what if he asked you to name the top 20 coaches of all time? Do you think you could come up with a list just as fast as you did for the athletes? If you were lucky, maybe you might spit out a couple legendary names like Lombardi or Wooden, but your pool of names would dry up pretty fast. And what would you even use to as criteria to create your coach list anyway? Wins? Championships? Sport Knowledge? Popularity? In any case, the question shows you great coaches are a rare breed. Not convinced? Think about your own experience in life with coaches. You have had both good and bad coaches. If you were really lucky, you may have even had one that you consider great. But regardless of which one you had, they all influenced your life. If you can agree a good or bad coach can either positively or negatively impact someone's life, Coach to Coach will ask you which coach do you want to be? Like it or not, Coach to Coach will teach you that you are a coach. Whether you are a teacher, parent, athlete, co-worker or boss, you are also a coach. Throughout your day, you are given constant opportunities to either coach someone up or down. To be a great coach is not just about the X's and O's of a sport, business or parenting, but also about the ability to bring more out of a person than they thought was possible. If being a coach is such an important job, you might wonder why the list of great coaches, parents and bosses seem so short? One reason could be that while many athletes are born with physical attributes that can lead them to greatness, a great coach requires much more than natural skill and talent. Great coaches aren't born, they're made. And this fact leads to the second reason for so few great coaches: there is a lack of educational resources to teach people the necessary strategies needed to become a more effective coach. Unfortunately, like money, marriage and parenting, coaching someone else doesn't come with manual. Martin Rooney's hope is that Coach to Coach quick and easy-to-read parable becomes that manual. Everyone is waiting for an inspirational coach. With Coach to Coach reveals the five major coaching secrets inside to gain the inspiration to stop waiting and become that coach"--
Online resource; title from digital title page (viewed on March 30, 2020).
Keywords: Coaching (Athletics); Entraînement (Sports); BUSINESS & ECONOMICS / Motivational; Coaching (Athletics)